ÉTUDE DE L’IMPACT DE L’UTILISATION DE L’AGENT DE MOUTURE MAGA C212 SUR LE PROCESSUS DE BROYAGE ET LA QUALITÉ DU CIMENT A LA SCB – CIMENT BOUCLIER - GBAGUIDI, Acakpo Nonvignon Magloire; Sanny, Farhanatou Akankè Féyichikè; Djidohokpin, Désiré Habib; Kpadonou , Dominique (International Journal of Scientific Research and Management (IJSRM), 2023)
The theme worked entitled “Study of the impact of the use of the MAGA C212 grinding agent on the grinding process and the quality of cement at SCB-Cement BOUCLIER”. The methodology adopted consisted of conducting the tests on the mini-mill and extrapolating the results obtained to the main mill. The tests are summarized in the determination of the load of the mini-crusher with regard to the wear of the balls, the optimum flow rates of the mini-crusher without and with grinding agent using a test sample of cement or white sample, the optimum dosage of grinding agent for an optimum flow rate, the production of cement under the optimum conditions identified and the physico-chemical characterization of the cement produced, namely the loss on ignition and the percentage of SO3, the Specific Blaine Surface Area, the percentage of Refusal on 80 µm and 160 sieve µm, and the compressive strengths at 2, 7 and 28 days. Thus, thanks to the use of MAGA C212 as a grinding agent under production conditions of 350 g/T and a constant flow rate of 15 kg/h, a significant improvement is induced compared to the control, on the fineness of 21, 12%, a reduction in refusal at 80 µm of 3.5% and a gain in resistance at 28 days of 13%. The optimal production conditions identified with the MAGA C212 grinding agent are 245 g of MAGA C212 per ton of material to be ground for 18 kg/h flow rate. At this dosage we obtain a gain of 20% in flow rate, an improvement in resistance at 28 days of 4.39% and an energy gain of 16.7%. Extrapolation of our experimental results to the real conditions of the main grinder allowed us to estimate an increase of 10% in yield, a reduction of 15% in the rate of MAGA C212 grinding agent, and a reduction of 8.35 % of the energy consumption of the main crusher.